2011
DOI: 10.1080/10683160903113699
|View full text |Cite
|
Sign up to set email alerts
|

Jurors believe interrogation tactics are not likely to elicit false confessions: will expert witness testimony inform them otherwise?

Abstract: Situational factors Á in the form of interrogation tactics Á have been reported to unduly influence innocent suspects to confess. This study assessed jurors' perceptions of these factors and tested whether expert witness testimony on confessions informs jury decision making. In Study 1, jurors rated interrogation tactics on their level of coerciveness and likelihood that each would elicit true and false confessions. Most jurors perceived interrogation tactics to be coercive and likely to elicit confessions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
80
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 39 publications
6
80
1
1
Order By: Relevance
“…Furthermore, Blandón‐Gitlin et al . () and Woody and Forrest () found that the presence of an expert reduced the frequency of guilty verdicts. It is important to note that in all four published studies to date, expert testimony has only been compared to control groups rather than to judicial instructions, another common safeguard.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, Blandón‐Gitlin et al . () and Woody and Forrest () found that the presence of an expert reduced the frequency of guilty verdicts. It is important to note that in all four published studies to date, expert testimony has only been compared to control groups rather than to judicial instructions, another common safeguard.…”
Section: Introductionmentioning
confidence: 98%
“…Four empirical studies to date have examined the effects of academic expert testimony in a disputed confession case (Blandón‐Gitlin, Sperry, & Leo, ; Moffa & Platania, , ; Woody & Forrest, ). Across these studies, the expert testimony contained similar descriptions of maximization and minimization techniques that have been linked to false confessions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…169 Research with mock juries has shown that confessions have more impact than other forms of evidence 170 and that jurors doubt that coercive techniques would ever cause an innocent suspect to confess. 171 There are a number of ways in which a RLA might prevent wrongful conviction. First, the presence of a legal adviser could discourage the police from using coercive interviewing tactics, a point that has already been discussed.…”
mentioning
confidence: 99%